ROUTLEDGE LIBRARY EDITIONS ([S.l.])
1 online resource
Keywords: This 26-volume set is a wide-ranging, time- and subject-spanning examination of the phenomenon of political protest. What drives people to take to the streets, and how do their governments respond? These questions and many more are analysed in areas as varied as sixteenth-century German peasant uprisings, revolutionary Russians at the Paris Commune, women protesting nuclear weapons at Greenham Common, and the role Christianity played in protests across the ages. An impressive reference resource, this set also looks at the policing of protests and official responses to them.